2012
DOI: 10.1136/bjophthalmol-2011-301078
|View full text |Cite
|
Sign up to set email alerts
|

Short term LASIK outcomes using the Technolas 217C excimer laser and Hansatome microkeratome in 46 708 eyes treated between 1998 and 2001

Abstract: The short-term results of a high-volume, multi-surgeon LASIK Corporation were comparable with those reported in the Food and Drug Administration clinical trials during the same period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…8 Studies 9,10 have shown that newly trained surgeons can achieve results similar to those of experienced surgeons. This supports the recommendation that surgeons should undergo a fellowship training program that includes observation of an experienced surgeon followed by supervision of their initial procedures 2,8,10,11 and shows the benefit of surgeons operating within a group adhering to a single protocol for quality-control purposes. Unless this is the case, it is very difficult to isolate the causes of differences in visual outcomes, something that patients would assume is minimal when attending a clinic for treatment.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…8 Studies 9,10 have shown that newly trained surgeons can achieve results similar to those of experienced surgeons. This supports the recommendation that surgeons should undergo a fellowship training program that includes observation of an experienced surgeon followed by supervision of their initial procedures 2,8,10,11 and shows the benefit of surgeons operating within a group adhering to a single protocol for quality-control purposes. Unless this is the case, it is very difficult to isolate the causes of differences in visual outcomes, something that patients would assume is minimal when attending a clinic for treatment.…”
Section: Discussionsupporting
confidence: 59%
“…previously developed a standardized surgical treatment protocol between 1998 and 2001 within a high-volume corporate practice. 2 This surgical treatment protocol was refined and adopted as the recommended surgical treatment protocol for use with the MEL 80 3 This training proved to be successful in showing that the visual outcomes were identical between the 2 surgeons for their first 200 consecutive LASIK procedures using the Visumax femtosecond laser. 8 The present study evaluated the level of standardization in surgical technique by comparing the application of this recommended LASIK surgical treatment protocol between 2 surgeons previously shown to produce equivalent visual outcomes, 8 each with 5 years' experience using the femtosecond and excimer lasers, through stepwise evaluation of surgical videos and statistical analysis.…”
Section: Online Videomentioning
confidence: 99%
“…Because of the limited literature on the small-incision lenticule extraction and femtosecond lenticule extraction techniques, all relevant articles were included in the review. Figures 1 to 3 were developed from summation and percentage data in several articles on small-incision lenticule extraction 2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and LASIK [26][27][28][29][30][31][32] ; attempts were made to ensure uniformity in the preoperative refractive parameters and other potentially confounding variables. The significant disproportion of available published literature on each technique resulted in a significantly larger portion of LASIK patients (n Z 36 822) than small-incision lenticule extraction patients (n Z 1759).…”
Section: Methodsmentioning
confidence: 99%
“…Our literature review found 26% of patients with postoperative corrected distance visual acuity (CDVA) equal to or more than 20/16, 62% equal to or more than 20/20, and 93% equal to or more than 20/40 after small-incision lenticule extraction 2,11-18,21,22 and 19%, 71%, and 95%, respectively, after LASIK (microkeratome and femtosecond laser assisted) (Figure 1). [26][27][28][29][30][31] Predictability Aggregation of our data reflects predictability values (at 6 months and 12 months) of 98% and 99%, respectively, for small-incision lenticule extraction 2,11,12,14-18,21,23,24 and 97% and 99%, respectively, for LASIK (microkeratome and femtosecond laser assisted) ( Figure 2). [26][27][28][29][30][31][32] The predictability reported by Lin et al 12 revealed similar consonance between the 2 procedures at 1 month and 3 months: 100% and 98.33% within G1.0 D, respectively, of small-incision lenticule extraction-treated eyes and 94.12% and 100%, within G1.0 D, respectively, of femtosecond laser-assisted LASIK-treated eyes.…”
Section: Refractive Outcomesmentioning
confidence: 95%
“…Reinstein and collaborators8 address this topic in this issue of the British Journal of Ophthalmology , in which the outcomes of a massive number of cases evaluated in the short term are reported. Even though the paper is elaborated on data created at the beginning of the last decade, the technique that they describe is still applied now in many corporate centres, both in terms of the microkeratome used and in excimer laser technology.…”
mentioning
confidence: 99%